Acute intestinal obstruction in children: a comparison of laparoscopic treatment and open surgery - Wu, Wei; Tan, Kezhe; Zheng, Lulu; Xu, Weijue; Lv, Zhibao; Liu, Jiangbin; Sun, Jun (Frontiers in Pediatrics, 2026)
ObjectiveThis study aimed to evaluate the clinical efficacy of laparoscopic surgery for acute small bowel obstruction (SBO) in children.MethodsThe retrospective study included children with acute SBO who were treated at Shanghai Children's Hospital from June 2014 to December 2023. Patients were categorized into one of the following two groups based on the operative approach they underwent: the laparoscopic surgery group and the open surgery group. Perioperative variables, including operative time, fasting duration, hospital stay, and complication rates, were evaluated. The primary outcome was length of hospital stay. Categorical variables were compared using the χ2 or Fisher's exact test, and continuous variables were analyzed using the t-test or Mann–Whitney U test, depending on the data distribution. A P-value < 0.05 was considered statistically significant.ResultsIn total, 40 patients underwent laparoscopic surgery and 40 underwent open surgery. Laparoscopic procedures were completed in 29 patients (72.5%), while 11 required conversions to open surgery. Compared with open surgery, laparoscopy resulted in a shorter hospital stay (median, 7.0 vs. 9.5 days; P = 1.1 × 10−5) and a shorter postoperative fasting period (median, 4.0 vs. 5.0 days; P = 0.011). A sensitivity analysis that excluded patients with a history of prior abdominal surgery still supported the overall findings and also showed a lower hospitalization cost in the laparoscopic group (median, 22,025.25 vs. 25,777.50 CNY; P = 0.013). The rates of intraoperative and postoperative complications were similar between the groups.ConclusionLaparoscopic surgery is a safe and effective option for pediatric acute SBO, offering faster recovery without increasing complication rates.